Preparation method of low-internal-resistance copper foil for lithium ion battery

By optimizing the surface characteristics and microstructure of copper foil of lithium batteries, the problem of excessive internal resistance of copper foil in traditional lithium batteries is solved, and higher conductivity and energy density is achieved, local overheating risk is reduced, and battery safety is improved. and stability meet the needs of fast charging and discharging.

CN119243270APending Publication Date: 2025-01-03JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411364454.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The internal resistance of copper foil in traditional lithium batteries is too large, resulting in insufficient performance of the battery in terms of high power output, fast charging and long battery life. It is easy to cause local overheating due to uneven current conduction, which affects safety and stability.

Method used

By controlling the surface roughness, thickness uniformity and microstructure of the copper foil, high-purity copper sulfate electrolyte and specific additives are used, combined with the grinding treatment and electrolysis process of the titanium cathode roller, the conductivity and microporous structure of the copper foil are optimized, and the microporous structure of the copper foil is reduced. Internal resistance and improve the energy density and magnification characteristics of the battery.

Benefits of technology

It significantly reduces the internal resistance of lithium batteries, improves the conductivity and energy density, reduces the risk of local overheating, improves the safety and stability of the battery, meets the needs of fast charging and discharging, and improves the overall performance consistency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243270A_ABST
    Figure CN119243270A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-internal-resistance copper foil for a lithium ion battery, which comprises the following specific steps of: 1, grinding a titanium cathode roller by using a grinding wheel of 50-600 meshes, removing an oxide layer, foreign matter points and the like on the surface of the cathode roller, and grinding by using a grinding wheel of 1000-1500 meshes; 2, the cathode roller falls into an electrolytic bath provided with an anode plate, and copper sulfate electrolyte is introduced into the electrolytic bath; and 4, a direct-current power supply is switched on, the current density of the power supply is 60-70 A / dm < 2 >, copper foil is subjected to electrolytic deposition on the arc-shaped cathode roller surface according to the Faraday principle, then the copper foil is subjected to acid pickling, water washing and passivation, and the lithium battery copper foil with the low internal resistance is obtained. On one hand, the problems of coating wrinkling and tab collapse in the battery preparation process are solved, on the other hand, the safety problem caused by excessive internal resistance and heating in the battery using process of an existing copper foil serving as a current collector is solved, and the performance such as the energy density and the rate characteristic of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic copper foil, in particular to a method for preparing a low internal resistance copper foil for lithium ion batteries. Background Art

[0002] In today's energy storage field, lithium batteries have become the core power source for many electronic devices and electric vehicles due to their high energy density, long cycle life and relative lightness. However, with the continuous development of technology and the growing demand for applications, the requirements for lithium battery performance are becoming more and more stringent.

[0003] In the composition of lithium batteries, copper foil, as the negative electrode current collector, is one of the most critical materials for lithium batteries. First of all, the size of its internal resistance directly affects the overall performance of the battery. Traditional lithium battery copper foil has certain limitations in conductivity and internal resistance control, and cannot fully meet the needs of new generation applications such as high power output, fast charging and long battery life. Secondly, the energy density and rate characteristics of traditional lithium batteries need to be improved, and some battery cells have shortcomings due to poor consistency. Thirdly, due to uneven current conduction, the battery is prone to local overheating areas, resulting in safety risks such as thermal runaway, and the safety and stability of the battery needs to be improved.

[0004] As a key material for lithium-ion batteries, copper foil has a relatively simple manufacturing process. The microstructure and surface characteristics of copper foil are not precisely controlled. For example, the surface flatness is insufficient, the roughness of the smooth and matte surfaces of the copper foil is too low or too high, and the roughness of the smooth and matte surfaces varies greatly. These problems will lead to problems such as wrinkling of the coating or collapse of the tabs during the preparation of lithium-ion batteries. After being prepared into a battery, the current will encounter greater resistance during the transmission process inside the battery, thereby affecting the battery's charge and discharge efficiency and power performance. At the same time, deficiencies in material purity and crystallinity also limit the conductive properties of copper foil.

[0005] A method for preparing low internal resistance copper foil for lithium batteries and its application, through in-depth research on the performance of negative electrode current collector copper foil required for lithium batteries, combined with research on copper foil's effect on current transmission in batteries and negative electrode material load, a new manufacturing process was invented. These technologies can more accurately control the thickness uniformity, roughness, crystal orientation and microscopic pore structure of copper foil, thereby significantly improving the problems of coating wrinkling and tab collapse in the battery preparation process, reducing the internal resistance of lithium batteries and improving conductivity. Summary of the invention

[0006] The present invention provides a low internal resistance copper foil for lithium ion batteries. The low internal resistance copper foil needs to control the roughness and smoothness of the copper foil surface, so the electroplating characteristics of the plating solution must be controlled. The optimal smoothness value of the plating solution requires a certain leveling agent concentration, a certain temperature and a certain current density.

[0007] A low internal resistance copper foil for lithium-ion batteries comprises a high-purity copper sulfate electrolyte, an electrolytic copper foil additive, and an electrolytic raw foil. On the one hand, the problems of coating wrinkling and tab collapse in the battery preparation process are improved; on the other hand, the safety problem caused by excessive internal resistance and heat generation when the existing copper foil is used as a current collector during battery use is solved, and the energy density, rate characteristics and other performance of the battery are improved.

[0008] The object of the present invention is to provide a method for preparing a low internal resistance copper foil for a lithium ion battery. The specific steps of the method for preparing a low internal resistance copper foil for a lithium ion battery are as follows:

[0009] Step 1: Grind the titanium cathode roller with a 50-600 mesh grinding wheel to remove the oxide layer and foreign matter on the surface of the cathode roller, and then grind it with a 1000-1500 mesh grinding wheel;

[0010] Step 2: The cathode roller is then dropped into an electrolytic cell equipped with an anode plate, and a copper sulfate electrolyte is introduced into the electrolytic cell, wherein the copper sulfate electrolyte contains 80-120 g / L of copper ions, 90-140 g / L of sulfuric acid, and 20-40 mg / L of chloride ions;

[0011] Step 3: Adding additives, the additives include a brightener with a content of 10-20 mg / L, an auxiliary brightener with a content of 5-8 mg / L, a leveler with a content of 1-2 mg / L, a super leveler with a content of 0.2-0.4 mg / L, an inhibitor with a content of 3-10 mg / L and a dispersant with a content of 0.1-0.3 mg / L;

[0012] Step 4: Connect a DC power supply with a current density of 60-70A / dm2, and electrolytically deposit copper foil on the arc-shaped cathode roller surface using the Faraday principle. Then, pickle, wash, and passivate the copper foil to obtain a lithium battery copper foil with low internal resistance.

[0013] Preferably, the copper sulfate electrolyte in step 2 enters the electrolysis machine after three-stage filtration, and the three-stage filtration refers to the diatomaceous earth filter performing the first-stage filtration, the security filter performing the second-stage filtration, and the precision filter performing the third-stage filtration.

[0014] Preferably, the temperature of the electrolyte during the electrolysis of the copper foil is 50-60°C; during the electrolysis of the copper foil, the upper liquid flow rate of the electrolyte is 40-50m3 / h.

[0015] Preferably, the brightener comprises an organic sulfide, specifically one or more of sodium alcoholthiopropane sulfonate or sodium polydisulfide propane sulfonate, sodium polydisulfide diethane sulfonate and sodium 3-mercapto-1-propane sulfonate;

[0016] The auxiliary brightener includes nitrogen-containing organic sulfide, specifically one or more of polyisothiourea propane sulfonic acid inner salt, sodium 3-benzothiazolyl-2-thiol propane sulfonate, and sodium dimethyl propane sulfonate.

[0017] Preferably, the leveling agent includes gelatin or collagen, or a mixture of the two, and the molecular weight of the collagen is 1000-5000 Daltons;

[0018] The super strong leveler is a heterocyclic compound, including one or more of tetrahydrothiazolidinethione, xylene pyridine, amino-4-methylbenzothiazole and tricyclazole.

[0019] Preferably, the inhibitor comprises one or more of sodium dodecyl sulfate or a polyether compound, the polyether compound comprising one of polyethylene glycol with a molecular weight of 4000-8000 or polyethylene glycol with a molecular weight of 400-1000;

[0020] The dispersant comprises one or more of hydroxymethyl cellulose or hydroxyethyl cellulose.

[0021] Preferably, the copper foil has a uniform grain structure, a flat structural profile, low surface roughness, a small difference in roughness between the smooth and matte surfaces of the copper foil, and an average grain size of 0.5-0.8 μm.

[0022] Preferably, the roughness Ra value of the smooth surface of the copper foil is less than 0.22 micrometers, the roughness Ra value of the matte surface is less than 0.20 micrometers, and the difference between the roughness of the smooth surface and the matte surface of the copper foil is within 0.03 micrometers.

[0023] Preferably, the elongation of the copper foil is greater than 12%, and the tensile strength of the copper foil is 300-400 MPa.

[0024] Preferably, the thickness of the copper foil is 6-10 μm.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] Reduce battery internal resistance: Low roughness means that the copper foil is in closer and smoother contact with the negative electrode active material and other components in the battery (such as diaphragms, etc.), and the current conduction path is smoother, which can effectively reduce the increase in local resistance caused by factors such as poor contact, thereby reducing the internal resistance of the entire battery.

[0027] Improve energy density: Thinner electrode layer: The surface of low-roughness copper foil is smoother, the negative electrode material is coated more evenly and can be coated thinner and tighter, more active materials can be accommodated in the same space, or when the active material is constant, the overall electrode thickness can be thinner, which is beneficial to improve the volume energy density and mass energy density of the battery.

[0028] Reducing invalid space: Due to good flatness, the layers are more closely fitted together during battery winding and other processes, reducing invalid space such as gaps caused by rough surfaces, contributing to improving battery energy density.

[0029] Improved rate performance: Due to the reduction of internal resistance, energy loss such as heat is reduced during high current charging and discharging. The battery can withstand a larger current density for charging and discharging, which improves the battery's charge and discharge rate performance and meets the needs of fast charging and discharging in power fields such as electric vehicles.

[0030] Reduce local overheating: Since the current conduction is uniform and the resistance is small, it is not easy to form overheating areas locally, thereby reducing safety risks such as thermal runaway of the battery due to local high temperature.

[0031] Stable interface: Low roughness helps maintain the stability of the interface of the negative electrode material during the cycle, and reduces problems such as the negative electrode material falling off the copper foil surface due to poor interface contact and uneven stress.

[0032] Uniform current distribution: The current on the copper foil surface is evenly distributed during the charge and discharge cycle, avoiding local excessive polarization and concentrated side reactions, thereby reducing electrochemical corrosion of the copper foil and negative electrode materials, and extending the battery cycle life.

[0033] Improve processing accuracy: In the process of electrode production, whether it is coating, rolling, slitting and other links, the low surface roughness of copper foil is more conducive to controlling process parameters and maintaining process stability and consistency, thereby reducing the defective rate.

[0034] Easier to clean: During the battery production process, if the copper foil surface is rough, it is easy for impurities to adhere to it. Low-roughness copper foil is relatively easier to clean, maintaining the cleanliness of the copper foil surface and preventing impurities from mixing into the battery and affecting performance and safety.

[0035] The difference in roughness between the smooth and matte surfaces of copper foil is small, which greatly improves the problems of coating wrinkling and cell tab collapse in the battery manufacturing process.

[0036] This can make mass-produced batteries have better consistency in performance, because the performance advantages brought by low roughness (such as internal resistance, energy density, etc.) will vary less between different batteries, helping to improve the overall performance and reliability of the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the structure of low resistance copper foil;

[0038] Figure 2 It is the cycle voltage-current curve diagram;

[0039] Figure 3This is a SEM image of the rough surface of ordinary lithium battery copper foil;

[0040] Figure 4 This is the SEM image of the rough surface of the low internal resistance lithium battery copper foil.

[0041] In the figure: 1- rough surface Ra of copper foil, 2- copper foil substrate, 3- smooth surface Ra of copper foil, 4- titanium cathode roller. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] The test methods for the microstructure and basic physical properties of the copper foil prepared in all embodiments of the present invention are as follows:

[0044] Scanning electron microscope (SEM) testing uses a focused electron beam to scan and image the sample surface point by point. The electron beam interacts with the sample to generate various physical signals, and the morphological information of the sample surface is obtained by detecting the signals.

[0045] Tensile strength and elongation test: According to the test method GB / T29847-2013, the tensile strength and elongation of the electrolytic copper foil were tested at a strain rate of 0.8 mm / s and room temperature (about 25°C) using the HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. The tensile test specimen is a strip specimen with a total length of 100 mm and a width of 15 mm. Repeat the measurement three times and take the average value as the final tensile strength and elongation of the sample.

[0046] The present invention provides a lithium battery copper foil with low internal resistance, which has uniform grain structure, flat structural profile, low surface roughness of the copper foil, small difference in roughness between the smooth and matte surfaces of the copper foil, and the like, and an average grain size of 0.5-0.8 microns. The low internal resistance copper foil is characterized in that the roughness Ra value of the smooth surface of the copper foil is less than 0.22 microns, the roughness Ra value of the matte surface is less than 0.20 microns, and the difference between the roughness of the smooth surface and the matte surface of the copper foil is within 0.03 microns.

[0047] First, the present invention controls the key parameters of the copper sulfate plating solution, including 80-120 g / L copper ions, 90-140 g / L sulfuric acid and 20-40 mg / L chloride ions in the electrolyte. The electrolyte is strictly filtered to electrolyze the foil, the electrolyte temperature of the foil is 50-60°C, and the upper liquid flow rate is 40-50 m3 / h.

[0048] Secondly, the present invention controls the roughness and consistency of the roller surface by grinding the surface of the titanium cathode roller, so that the roughness of the copper foil electroplated on the surface of the titanium cathode roller meets the characteristics of a low internal resistance lithium battery copper foil of the present invention. The grinding treatment of the titanium cathode roller includes grinding with a 50-600 mesh grinding wheel and then grinding with a 1000-1500 mesh grinding wheel. The current density of the power supply during electroplating is 60-70A / dm 2 The copper foil is pickled, washed with water and passivated to obtain lithium battery copper foil with low internal resistance.

[0049] Thirdly, the key improvement point 1 of the present invention is that the nucleation of the copper foil is optimized by adding additives to the copper sulfate electrolyte. Specifically, a certain concentration of brightener and inhibitor produces synergistic and competitive effects in the electrochemical reaction, so that the deposited copper foil grains are uniform and the grain size is moderate.

[0050] Fourth, the key improvement point 2 of the present invention is to add a super strong leveler to the traditional collagen-based leveler to improve the leveling performance. If a heterocyclic compound containing N in the molecule is selected and the surrounding substituents are changed, the effect of the substituents on the leveling ability and the adsorption of the leveler on the cathode copper and the inhibition of copper ion discharge can be found. Through experiments and research, it is shown that the leveling ability can be improved by more than 50% by introducing a compound containing phenyl in the plating solution, and a high smoothness value can be maintained in a wider concentration range.

[0051]

[0052] The above formula is used to measure the leveling agent capacity using the cyclic voltage current stripping method (CVS method). This method is to rotate the disk platinum electrode to make the electrode potential change cyclically, and copper is alternately deposited and dissolved on the electrode. Figure 2 The cyclic voltage-current curve shown in the figure. The anodic peak during the positive potential sweep in the figure is the dissolution peak of the copper deposited on the electrode. Figure 2 The maximum area of ​​the dissolution peak shown in curve 1 is As. After adding the leveling agent, Figure 2 The maximum area of ​​the dissolution peak shown in curve 2 is Ar, and As-Ar is equivalent to the difference in the amount of copper plating suppressed by the leveling agent, which is used to calculate the leveling ability of different leveling agents.

[0053] Embodiment 1: A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then stored in an electrolyte tank. Additives and hydrochloric acid are added to the electrolyte tank.

[0054] The copper ion concentration in the electrolyte tank is 90 g / L, the sulfuric acid content is 115 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 57°C.

[0055] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 10 mg / L, sodium polyisothiourea propane sulfonate at 10 mg / L, collagen with a molecular weight of 2000 Daltons at 11 mg / L, amino-4-methylbenzothiazole at 0.5 mg / L, polyethylene glycol with a molecular weight of 6000 at 5 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0056] The surface of the titanium cathode roller was ground once with a 300-mesh grinding wheel, once with a 600-mesh grinding wheel, and then ground for 40 minutes with a 1000-mesh non-woven grinding wheel.

[0057] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally obtain the finished copper foil. The finished copper foil has a tensile strength of 352 MPa and an elongation of 15.1% measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.28 microns, and the average roughness Ra of the matte surface is 0.18 microns. The average grain size is 0.6 microns as analyzed by SEM testing.

[0058] Example 2: A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then stored in an electrolyte tank. Additives and hydrochloric acid are added to the electrolyte tank.

[0059] The copper ion concentration in the electrolyte tank is 90 g / L, the sulfuric acid content is 115 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 57°C.

[0060] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 15 mg / L, sodium polyisothiourea propane sulfonate at 5 mg / L, collagen with a molecular weight of 2000 Daltons at 8 mg / L, amino-4-methylbenzothiazole at 1 mg / L, polyethylene glycol with a molecular weight of 6000 at 10 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0061] The surface of the titanium cathode roller was ground twice using a 300-mesh grinding wheel, then ground twice using a 600-mesh grinding wheel, and then ground for 60 minutes using a 1000-mesh non-woven grinding wheel.

[0062] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally produce the finished copper foil. The finished copper foil has a tensile strength of 334 MPa and an elongation of 14.4% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.22 microns, and the average roughness Ra of the matte surface is 0.16 microns. The average grain size is 0.8 microns as analyzed by SEM testing.

[0063] Example 3: A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then stored in an electrolyte tank. Additives and hydrochloric acid are added to the electrolyte tank.

[0064] The copper ion concentration in the electrolyte tank is 93 g / L, the sulfuric acid content is 110 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 55°C.

[0065] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 15 mg / L, sodium polyisothiourea propane sulfonate at 5 mg / L, collagen with a molecular weight of 2000 Daltons at 6 mg / L, amino-4-methylbenzothiazole at 1.5 mg / L, polyethylene glycol with a molecular weight of 6000 at 8 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0066] The surface of the titanium cathode roller was ground twice using a 300-mesh grinding wheel, then ground twice using a 600-mesh grinding wheel, and then ground for 90 minutes using a 1500-mesh non-woven grinding wheel.

[0067] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally obtain the finished copper foil. The finished copper foil has a tensile strength of 349 MPa and an elongation of 15.8% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.20 microns, and the average roughness Ra of the matte surface is 0.18 microns. The average grain size is 0.7 microns as analyzed by SEM testing.

[0068] Example 4: A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then stored in an electrolyte tank. Additives and hydrochloric acid are added to the electrolyte tank.

[0069] The copper ion concentration in the electrolyte tank is 93 g / L, the sulfuric acid content is 115 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 53°C.

[0070] Add additives to the electrolyte storage tank, 20 mg / L sodium polydisulfide propane sulfonate, 10 mg / L sodium polyisothiourea propane sulfonate, 4 mg / L collagen with a molecular weight of 2000 Daltons, 2 mg / L amino-4-methylbenzothiazole, 5 mg / L polyethylene glycol with a molecular weight of 6000, and 1 mg / L hydroxyethyl cellulose. The above additives are added according to the volume concentration ratio of the electrolyte.

[0071] The surface of the titanium cathode roller was ground once with a 300-mesh grinding wheel, once with a 600-mesh grinding wheel, and then ground for 120 minutes with a 1500-mesh non-woven grinding wheel.

[0072] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally produce the finished copper foil. The finished copper foil has a tensile strength of 357 MPa and an elongation of 14.6% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.22 microns, and the average roughness Ra of the matte surface is 0.28 microns. The average grain size is 0.6 microns as analyzed by SEM testing.

[0073] Comparative Example 1: Comparative Example 1 is the first comparison of Example 3. A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the copper using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then enters an electrolyte tank for storage, and additives and hydrochloric acid are added to the electrolyte tank.

[0074] The copper ion concentration in the electrolyte tank is 93 g / L, the sulfuric acid content is 110 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 55°C.

[0075] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 15 mg / L, sodium polyisothiourea propane sulfonate at 5 mg / L, collagen with a molecular weight of 2000 Daltons at 15 mg / L, polyethylene glycol with a molecular weight of 6000 at 6 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0076] The surface of the titanium cathode roller was ground twice using a 300-mesh grinding wheel, then ground twice using a 600-mesh grinding wheel, and then ground for 90 minutes using a 1500-mesh non-woven grinding wheel.

[0077] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally obtain the finished copper foil. The finished copper foil has a tensile strength of 352 MPa and an elongation of 15.4% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.23 microns, and the average roughness Ra of the matte surface is 0.16 microns. The average grain size is 0.7 microns as analyzed by SEM testing.

[0078] Comparative Example 2: Comparative Example 2 is a second comparison of Example 3. A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank by a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter to enter an electrolyte tank for storage, and additives and hydrochloric acid are added to the electrolyte tank.

[0079] The copper ion concentration in the electrolyte tank is 93 g / L, the sulfuric acid content is 110 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 55°C.

[0080] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 15 mg / L, sodium polyisothiourea propane sulfonate at 5 mg / L, collagen with a molecular weight of 2000 Daltons at 4 mg / L, amino-4-methylbenzothiazole at 1.5 mg / L, polyethylene glycol with a molecular weight of 6000 at 8 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0081] The surface of the titanium cathode roller was ground once with a 300-mesh grinding wheel, once with a 600-mesh grinding wheel, and then ground for 60 minutes with a 1000-mesh non-woven grinding wheel.

[0082] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally obtain the finished copper foil. The finished copper foil has a tensile strength of 350 MPa and an elongation of 15.5% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.22 microns, and the average roughness Ra of the matte surface is 0.25 microns. The average grain size is 0.7 microns as analyzed by SEM testing.

[0083] Comparative Example 3: A cathode copper plate or copper wire with a purity of ≥99.95% is added to a copper dissolving tank containing sulfuric acid, and high-temperature air is blown into the tank using a screw fan to dissolve the copper to prepare a copper sulfate solution. The copper sulfate electrolyte is filtered through a diatomaceous earth filter, a security filter, and a precision filter and then stored in an electrolyte tank. Additives and hydrochloric acid are added to the electrolyte tank.

[0084] The copper ion concentration in the electrolyte tank is 90 g / L, the sulfuric acid content is 115 g / L, and the chloride ion concentration in the electrolyte is 25 mg / L. The flow rate of the electrolyte entering the electrolytic foil is 45 cubic meters per hour, and the temperature is 52°C.

[0085] Add additives to the electrolyte storage tank, sodium polydisulfide propane sulfonate at 15 mg / L, sodium polyisothiourea propane sulfonate at 5 mg / L, collagen with a molecular weight of 2000 Daltons at 6 mg / L, amino-4-methylbenzothiazole at 1.5 mg / L, polyethylene glycol with a molecular weight of 6000 at 8 mg / L, and hydroxyethyl cellulose at 1 mg / L. The above additives are added according to the volume concentration ratio of the electrolyte.

[0086] The surface of the titanium cathode roller was ground twice using a 300-mesh grinding wheel, then ground twice using a 600-mesh grinding wheel, and then ground for 90 minutes using a 1500-mesh non-woven grinding wheel.

[0087] The direct current passed during the electrolysis of copper foil has a current density of 60A / square decimeter, producing 8-micron copper foil. The raw foil is passivated with an anti-oxidation liquid to finally obtain the finished copper foil. The finished copper foil has a tensile strength of 342 MPa and an elongation of 15.8% as measured by a universal material testing machine. The average roughness Ra of the smooth surface of the copper foil is 0.20 microns, and the average roughness Ra of the matte surface is 0.25 microns. The average grain size is 0.8 microns as analyzed by SEM testing.

[0088] Table 1 below lists the test results of basic physical properties, roughness and microscopic grain size of lithium battery copper foil samples produced according to various embodiments of the present invention and comparative examples.

[0089] Table 1 Summary of Examples and Comparative Examples

[0090]

[0091] From the examples, the lithium battery copper foil produced under the conditions of Example 3 has stable physical properties, a low smooth and matte surface roughness Ra, and a small difference in the smooth and matte surface roughness Ra, meeting the parameter requirements for low internal resistance lithium battery copper foil.

[0092] Example 3 and Comparative Example 1 are samples produced under the same working conditions. The main difference is that the comparative example does not add the super leveling agent amino-4-methylbenzothiazole, but only increases the concentration of collagen and reduces the concentration of the wetting agent polyethylene glycol. The difference value of the roughness Ra of the smooth and matte surface increases relative to that of Example 3, so Comparative Example 1 does not achieve the ideal effect.

[0093] Comparative Example 2 and Example 3 are samples produced under the same copper sulfate electrolyte and additive conditions. Comparative Example 2 adjusted the surface treatment parameters of the titanium cathode roller, but failed to achieve the expected effect.

[0094] Comparative Example 3 is the third adjustment comparison of Example 3. It is a sample produced under the same titanium cathode roller surface treatment and additive conditions. Comparative Example 2 increases the acid ion concentration and reduces the copper ion concentration, lowers the electrolyte temperature, and the difference in the roughness Ra of the smooth surface increases relative to Example 3, so Comparative Example 3 does not achieve the ideal effect.

[0095] In summary, low internal resistance copper foil needs to control the roughness and smoothness of the copper foil surface, which requires controlling the electroplating characteristics of the plating solution, controlling the key copper acid concentration in the copper sulfate electrolyte, the electrolyte temperature, and the surface treatment method of the titanium cathode roller. The key is that the plating solution also needs to contain a super strong leveling agent and cooperate with other additives to produce the low internal resistance lithium battery copper foil described in the present invention.

[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a low internal resistance copper foil for a lithium ion battery, characterized in that: The specific steps of the method for preparing the low internal resistance copper foil for lithium ion batteries are as follows: Step 1: Grind the titanium cathode roller with a 50-600 mesh grinding wheel to remove the oxide layer and foreign matter on the surface of the cathode roller, and then grind it with a 1000-1500 mesh grinding wheel; Step 2: The cathode roller is then dropped into an electrolytic cell equipped with an anode plate, and a copper sulfate electrolyte is introduced into the electrolytic cell, wherein the copper sulfate electrolyte contains 80-120 g / L of copper ions, 90-140 g / L of sulfuric acid, and 20-40 mg / L of chloride ions; Step 3: Adding additives, the additives include a brightener with a content of 10-20 mg / L, an auxiliary brightener with a content of 5-8 mg / L, a leveler with a content of 1-2 mg / L, a super leveler with a content of 0.2-0.4 mg / L, an inhibitor with a content of 3-10 mg / L and a dispersant with a content of 0.1-0.3 mg / L; Step 4: Connect a DC power supply with a current density of 60-70A / dm2, and electrolytically deposit copper foil on the arc-shaped cathode roller surface using the Faraday principle. Then, pickle, wash, and passivate the copper foil to obtain a lithium battery copper foil with low internal resistance.

2. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The copper sulfate electrolyte in step 2 enters the electrolysis machine after three-stage filtration. The three-stage filtration refers to the diatomaceous earth filter performing the first-stage filtration, the security filter performing the second-stage filtration, and the precision filter performing the third-stage filtration.

3. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The temperature of the electrolyte for electrolyzing the copper foil is 50-60°C; during the electrolyzing copper foil process, the upper liquid flow rate of the electrolyte is 40-50m3 / h.

4. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The brightener includes an organic sulfide, specifically one or more of sodium alcoholthiopropane sulfonate or sodium polydisulfide propane sulfonate, sodium polydisulfide diethane sulfonate and sodium 3-mercapto-1-propane sulfonate; The auxiliary brightener includes nitrogen-containing organic sulfide, specifically one or more of polyisothiourea propane sulfonic acid inner salt, sodium 3-benzothiazolyl-2-thiol propane sulfonate, and sodium dimethyl propane sulfonate.

5. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The leveling agent includes gelatin or collagen or a mixture of the two, and the molecular weight of the collagen is 1000-5000 Daltons; The super strong leveler is a heterocyclic compound, including one or more of tetrahydrothiazolidinethione, xylene pyridine, amino-4-methylbenzothiazole and tricyclazole.

6. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The inhibitor includes one or more of sodium dodecyl sulfate or a polyether compound, wherein the polyether compound includes one of polyethylene glycol with a molecular weight of 4000-8000 or polyethylene glycol with a molecular weight of 400-1000; The dispersant comprises one or more of hydroxymethyl cellulose or hydroxyethyl cellulose.

7. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The copper foil has a uniform grain structure, a flat structural profile, low surface roughness, small difference in roughness between the smooth and matte surfaces, and an average grain size of 0.5-0.8μm.

8. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The roughness Ra value of the smooth surface of the copper foil is less than 0.22 microns, the roughness Ra value of the matte surface is less than 0.20 microns, and the difference in roughness between the smooth and matte surfaces of the copper foil is within 0.03 microns.

9. The method for preparing a low internal resistance copper foil for a lithium ion battery according to claim 1, characterized in that: The elongation of the copper foil is greater than 12%, and the tensile strength of the copper foil is 300-400MPa.

10. The method for preparing a low internal resistance copper foil for lithium ion batteries according to claim 1, characterized in that: The thickness of the copper foil is 6-10 μm.

Citation Information

Cited By

  • Copper foil preparation system with double electrolytic baths, electrolytic copper foil and preparation method

    CN120291167A

  • Copper foil preparation system with double electrolytic cells, electrolytic copper foil and preparation method

    CN120291167B

  • Preparation method of carbon-coated copper foil

    CN120945446A

  • A method for producing a carbon-coated copper foil

    CN120945446B

  • Electrolyte and method for reducing unit electricity consumption of raw foil of lithium battery copper foil and lithium battery copper foil

    CN121250476A